Microwave-Assisted Synthesis of p[n]arene Catalyzed by KOH - Li Baozhi; Yang Gengliang; Zhang Jinsong; Duan Kefang (E-Journal of Chemistry)
The paper researched the synthesis of p-methylcalix[6]arene and p-tertbutylcalix[8]arene catalyzed by KOH in moderate yields under microwave irradiation. The effects of different factors on this condensation reaction have been discussed. Compared with classical method, this method had some merits such as easy obtaining the raw materials, short reaction route, simple and convenient aftertreatment, being beneficial to environmental protection.